Disrupted Spontaneous Neural Activity in Patients With Thyroid-Associated Ophthalmopathy: A Resting-State fMRI Study Using Amplitude of Low-Frequency Fluctuation - Chen, Wen; Wu, Qian; Chen, Lu; Zhou, Jiang; Chen, Huan-Huan; Xu, Xiao-Quan; Hu, Hao; Wu, Fei-Yun (Frontiers in Human Neuroscience, 2021)
Purpose: To investigate the brain functional alteration in patients with thyroid-associated ophthalmopathy (TAO) by evaluating the spontaneous neural activity changes using resting-state functional magnetic resonance imaging (rs-fMRI) with the amplitude of low-frequency fluctuation (ALFF) method. Methods: The rs-fMRI data of 30 TAO patients (15 active and 15 inactive) and 15 healthy controls (HCs) were included for analyses. The ALFF values were calculated and compared among groups. Correlations between ALFF values and clinical metrics were assessed. Results: Compared with HCs, active TAOs showed significantly decreased ALFF values in the left middle occipital gyrus, superior occipital gyrus and cuneus. Compared with inactive TAOs, active TAOs showed significantly increased ALFF values in the bilateral precuneus. Additionally, inactive TAOs showed significantly decreased ALFF values in the left middle occipital gyrus, superior occipital gyrus, cuneus and bilateral precuneus than HCs. The ALFF value in right precuneus of TAOs was positively correlated with clinical activity score (r = 0.583, P < 0.001) and Mini-Mental State Examination (MMSE) score (r = 0.377, P = 0.040), and negatively correlated with disease duration (r = -0.382, P = 0.037). Moreover, the ALFF value in left middle occipital gyrus of TAOs was positively correlated with visual acuity (r = 0.441, P = 0.015). Conclusions: TAO patients had altered spontaneous brain activities in the left occipital lobe and bilateral precuneus. The neuropsychological aspect of the disease should be noticed during clinical diagnosis and treatment.